2015
DOI: 10.1055/s-0034-1395519
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Instability with Plyometric Training in Sub-elite Adolescent Soccer Players

Abstract: The purpose of this study was to investigate the effects of plyometric training on stable (SPT) vs. highly unstable surfaces (IPT) on athletic performance in adolescent soccer players. 24 male sub-elite soccer players (age: 15±1 years) were assigned to 2 groups performing plyometric training for 8 weeks (2 sessions/week, 90 min each). The SPT group conducted plyometrics on stable and the IPT group on unstable surfaces. Tests included jump performance (countermovement jump [CMJ] height, drop jump [DJ] height, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 21 publications
(42 reference statements)
4
104
0
8
Order By: Relevance
“… %Δ, Percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; CSTS, core strength training on stable surface; CSTU, core strength training on unstable surface; EE, elbow extension; EF, elbow flexor; ET, elastic tubing; Ex, exercises; FFM, fat free mass; Freq, frequency; FW, free weight; Int, intensity; Isok, isokinetic; Isom, isometric; Isot, isotonic; KE, knee extension; KF, knee flexion; kg, kilogram; m, meter; Med, Medicine; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; PBT, plyometric training before balance training; PE, physical education students; PHV, peak height velocity; Post, post-test; Power, power measures; Pre, pre-test; PT, peak torque; Reps, repetitions; RM, repetition maximum; RPE, rating of perceived exertion; s, second; SD, standard deviation; Strength, strength measures; T, trained youth; TMS, trunk muscle strength; Tr, training status; U, untrained youth; Var, varied; Wks, weeks . Additional Citations for Table 2A are found in the text reference list (Hettinger, 1958; Funato et al, 1986; Sewall and Micheli, 1986; Weltman et al, 1986; Blimkie, 1989; Ozmun et al, 1994; DeRenne et al, 1996; Gorostiaga et al, 1999; Sadres et al, 2001; Flanagan et al, 2002; Pikosky et al, 2002; Tsolakis et al, 2004; Drinkwater et al, 2005; Benson et al, 2007; Faigenbaum et al, 2007a, 2014, 2015; Channell and Barfield, 2008; Rhea et al, 2008; Teng et al, 2008; Chelly et al, 2009; Dorgo et al, 2009; Lubans et al, 2010; Velez et al, 2010; Wong et al, 2010; Ebada, 2011; Granacher et al, 2011a,b, 2014, 2015; Ignjatovic et al, 2011; Muehlbauer et al, 2012; Santos and Janeira, 2012; Moore et al, 2013; Moraes et al, 2013; Sander et al, 2013; Coskun and Sahin, 2014; Ferrete et al, 2014; Pesta et al, 2014; Piazza et al, 2014; Dalamitros et al, 2015; Gonzalez-Badillo et al, 2015; dos Santos Cunha et al, 2015; Sarabia et al, 2015; Tran et al, 2015; Eather et al, 2016; Harries et al, 2016; Lloyd et al, 2016; Negra et al, 2016; Prieske et al, 2016; Rodriguez-Rosell et al, …”
Section: Resultsmentioning
confidence: 99%
“… %Δ, Percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; CSTS, core strength training on stable surface; CSTU, core strength training on unstable surface; EE, elbow extension; EF, elbow flexor; ET, elastic tubing; Ex, exercises; FFM, fat free mass; Freq, frequency; FW, free weight; Int, intensity; Isok, isokinetic; Isom, isometric; Isot, isotonic; KE, knee extension; KF, knee flexion; kg, kilogram; m, meter; Med, Medicine; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; PBT, plyometric training before balance training; PE, physical education students; PHV, peak height velocity; Post, post-test; Power, power measures; Pre, pre-test; PT, peak torque; Reps, repetitions; RM, repetition maximum; RPE, rating of perceived exertion; s, second; SD, standard deviation; Strength, strength measures; T, trained youth; TMS, trunk muscle strength; Tr, training status; U, untrained youth; Var, varied; Wks, weeks . Additional Citations for Table 2A are found in the text reference list (Hettinger, 1958; Funato et al, 1986; Sewall and Micheli, 1986; Weltman et al, 1986; Blimkie, 1989; Ozmun et al, 1994; DeRenne et al, 1996; Gorostiaga et al, 1999; Sadres et al, 2001; Flanagan et al, 2002; Pikosky et al, 2002; Tsolakis et al, 2004; Drinkwater et al, 2005; Benson et al, 2007; Faigenbaum et al, 2007a, 2014, 2015; Channell and Barfield, 2008; Rhea et al, 2008; Teng et al, 2008; Chelly et al, 2009; Dorgo et al, 2009; Lubans et al, 2010; Velez et al, 2010; Wong et al, 2010; Ebada, 2011; Granacher et al, 2011a,b, 2014, 2015; Ignjatovic et al, 2011; Muehlbauer et al, 2012; Santos and Janeira, 2012; Moore et al, 2013; Moraes et al, 2013; Sander et al, 2013; Coskun and Sahin, 2014; Ferrete et al, 2014; Pesta et al, 2014; Piazza et al, 2014; Dalamitros et al, 2015; Gonzalez-Badillo et al, 2015; dos Santos Cunha et al, 2015; Sarabia et al, 2015; Tran et al, 2015; Eather et al, 2016; Harries et al, 2016; Lloyd et al, 2016; Negra et al, 2016; Prieske et al, 2016; Rodriguez-Rosell et al, …”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have emphasized the potentially favorable influence of training on an unstable surface upon balance and agility [7,8,18,19], offering as it does specific training in the challenges faced during actual play on uneven and soggy fields. However, depending on the age, maturity and training status of athletes, the likelihood that the sandy surface corrects some overtraining may also be foreshadowed by the increase of muscle strength seen with the tapering of a standard plyometric regimen [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some research has compared the effectiveness of training on stable and unstable surfaces. Negra et al [6] and Granacher et al [7] found comparable gains on measures of muscle power (e.g., countermovement and standing jumps, sprint speeds, dynamic balance, and agility tests) on stable vs. unstable surfaces in prepubertal male soccer players. Arazi et al [8] also observed similar improvements in vertical jumps [ [8].…”
Section: Introductionmentioning
confidence: 92%
“…The specific methods for developing the speed used in the study are based on repetitions (specific efforts at maximum speed or submaximum, under normal, relieved, difficult conditions) [4], on varied efforts [5,6,7,8,9]. Methods of skill development have taken into account the complexity of coordination of motor actions and spatial, temporal and movement accuracy [10,11,12]. Methods of training for the development of motor skills: Interval training [13]and circuit training [14,15,16,17].…”
Section: Methodsmentioning
confidence: 99%